Analysing The Causes of Management and Production Delays in The Implementation of Construction Project Work - Putri Lynna Luthan; Nathanael Sitanggang; Syahreza Alvan; Wisnu Prayogo (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to analyse the causes of delays in the implementation of construction projects caused by management (owners/consultants) and production (contractors). The research sample consists of 56 respondents who are directly involved in the implementation of construction projects (owners, consultants, contractors, field supervisors, and estimators). The quantitative data analysis technique used was descriptive analysis technique, while the qualitative data obtained by interviewing 5 construction project experts was analysed by qualitative descriptive method. To analyse the causes of delays in project implementation, an analysis technique using the Relative Importance Index (RII) formula was used with a reference value of RII> 0.710. The results showed that 1) the average RII on management factors was 0.895> 0.710. This means that management factors (owner/consultant) can cause delays in the implementation of construction projects; 2) the average RII on production factors is 0.917> 0.710. This means that production factors (contractors) can cause delays in the implementation of construction projects. This means that production factors (contractors) can cause delays in the implementation of construction projects. This research is directly useful for construction service providers and contributes to the development of Project / Construction Management science.